Inovasi Pembelajaran Berbasis Proyek Untuk Meningkatkan Kecerdasan Kognitif Anak Usia 5 – 6 Tahun di TK Islam Amar Ma’ruf - Khotimah, Khusnul; Nisa, Shifa Choerun; Imamah, Imamah (CV. ITTC INDONESIA, 2024)
This study aims to explore the impact of implementing project-based learning on the cognitive intelligence of children aged 5-6 years at Amar Ma'ruf Islamic Kindergarten. Project-based learning is applied through a constructivist model, allowing children to actively engage and build their own understanding through direct experiences. The research employs a qualitative approach with a case study design, gathering in-depth data through continuous observations, interviews with teachers and parents, and documentation of children's project activities. The results reveal that children involved in project-based learning show significant improvement in critical thinking skills, creativity, and social abilities, including collaboration and communication. For instance, in a project themed